2018
DOI: 10.1016/j.maturitas.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and temperature extremes: A review of heat- and cold-related morbidity and mortality concerns of municipalities

Abstract: Cold and hot weather are associated with mortality and morbidity. Although the burden of temperature-associated mortality may shift towards high temperatures in the future, cold temperatures may represent a greater current-day problem in temperate cities. Hot and cold temperature vulnerabilities may coincide across several personal and neighborhood characteristics, suggesting opportunities for increasing present and future resilience to extreme temperatures. We present a narrative literature review encompassin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 36 publications
2
40
0
1
Order By: Relevance
“…The adverse effect of extreme temperature on human health has been intensively reported during the last decade [ 1 , 2 ]. Epidemiological evidence shows that both high and low temperature were associated with increased mortality and morbidity in western, Asian and African countries [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effect of extreme temperature on human health has been intensively reported during the last decade [ 1 , 2 ]. Epidemiological evidence shows that both high and low temperature were associated with increased mortality and morbidity in western, Asian and African countries [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of cold temperatures on mortality is a phenomenon that is not exclusive to northern countries. It has also been reported across different temperature zones, where recent studies have shown that more temperature-attributable deaths are caused by cold than by heat [7,8,9], and effect estimates (relative risks—RRs) for cold are higher than those for heat [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress is receiving a lot of coverage in media as global temperature increases and a large part of the global population experience exclusively heat stress, however mortality is higher in winter than in summer in temperate climate [43,44]. Excess morbidity and mortality is attributed to a varied winter weather which is forecasted by climate models even though the global mean temperature is expected to rise [45].…”
Section: Thermal Exposure and Health Risks In A Changing Climatementioning
confidence: 99%